The PENGARUH KUALITAS PRODUK DAN PELAYANAN TERHADAP KEPUASAN KONSUMEN PT. KELOLA PRINTING JAKARTA TIMUR - Marsadi Aras (Mediastima, 2020)
ABSTRACT This research aims to determine the influence of product quality and work service on customer satisfaction, simultaneously and partially. The object of research is consumers of PT. Kelola Printing Jakarta Timur. The number of respondents was 83. The data collection technique uses random sampling. This study uses quantitative method by first establishing the concept in the variables based on the relevant theory. Furthermore, the data collection technique used a questionnaire. The survey method is used in the sampling process from a predetermined population. Based on the results of analysis, it is known that the variable of product quality and work service quality have an effect on customer satisfaction simultaneously. The F table value is 104, 237 with a significance of 0.00. The product quality and service quality variables influence the consumer satisfaction by 72.3%, while the rest is influenced by other variables not analyzed or not included in the model. The product quality variable significantly influences consumer satisfaction, based on the value of t-count of 12.719 and a significance value of 0.000. the product quality variable influences consumer satisfaction by 64.7%, the rest is influenced by other variables. The service quality variable significantly influences the satisfaction, because the value of t-count is 7.383 and the significance value is 0.000. The service quality variable influences the consumer satisfaction by 40.2%, while the rest is influenced by other variables